Supply Chain Management Performance Measurement. Case Studies from Developing Countries - Sinoimeri, Dea; Teta, Jonida (International Journal of Membrane Science and Technology, 2023)
Supply chain management is critical for companies (suppliers, distributors, manufacturers, and retailers) and researchers. Supply chain sustainability is important in Developing Countries. To evaluate the performance of supply chains in companies located in Developing Countries like Albania and Kosovo, this article will examine the findings of the Supply Chain Operation Reference (SCOR) model. Utilizing the SCOR model can improve a company’s chances of survival and rivalry in the market. The selection of Performance Attributes appears to be the standard for measuring performance. By contrast, Snorm De Boer normalization equates the importance of Key Performance Indicators (KPIs), the Analytical Hierarchy Process (AHP) calculates the weighted criteria of KPIs, and Objective Matrix (OMAX) analyzes the measurement results of the KPIs. This article identifies unexplored areas for future research that will be beneficial in the field of supply chain management, such as the creation of supply chain performance metrics, creation of a model that is tightly integrated into the supply chain, and handling supply chain-related problems and issues.